Pola Kunjungan Wisatawan Pada Daya Tarik Wisata Di Kawasan Sarbagita - I Putu Dody Andrian; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2018)
In this research aims to the pattern of tourists’ visit on tourists attraction in the area of Sarbagita. This reseach was carried out to find out the movement of tourists in visiting one to other tourist destinations which existed in the area of Sarbagita. This research was through several stages, namely: identification of characteristic of tourists who were visiting Sarbagita area and how about the pattern type of their visit. Next it was studying how the path of tourists’ movement who were visiting tourist attractions existed in Sarbagita area. Data collection technique was using observation, interview, distribution of 100 questionnaires, literature study and documentation. Informant determination technique was using accidental sampling. The result of research showed that tourists who were visiting various tourist destinations existed in Sarbagita area with the highest number of visits was in tourist attraction of Tanah Lot, Uluwatu, Kuta Beach, Sanur Beach, Bedugul, Ceking Rice Terrace and Pandawa Beach. The pattern of tourists’ visit who were visiting Sarbagita area had 4 types of visits, namely the first wasm “Single Destination With or Without side Trips” , the second was “Transit Leg and Circle Tour at a Destination” , the third was “Circle Tour With or Without Multiple Access , Egress Points ; Different Itinerary Styles Possible at Different Destination Areas”, and the fourth was “Hub and Spoke Style”. Keywords: Tourists, Pattern, Visit, Tourist Destination, Area